Upaya Orang Tua Dalam Menumbuhkan Karakter Religius Pada Anak Melalui Pembiasaan Menggunakan Operant Conditioning - Noor Alfi Fajriyani; Luluk Maululah; Irfan Irfan (IAIN Manado, 2023)
The Role of Parents in Developing Religious Character Through Habituation Using Operant Conditioning. This research aims to explain the implementation of habituation to religious activities using operant conditions as a form of effort to foster religious character in children. By using a qualitative approach, the phenomenological method, located in Kab. Sumenep, Madura. Data collection using observation techniques as an observer and semi-structured interviews. The results of the research show that there are four forms of parental efforts to foster religious character in children through habituation using operant conditioning, namely; the habit of praying, reciting the Koran, fasting, and giving alms on Fridays. This habit is carried out every day consistently and continuously and without forcing it. In this habituation, there is a contribution between the parents and grandparents of KF so that the process of growing religious character in KF can be in line. As a form of motivation for the emergence of family behavior, it reinforces the form of rewards and punishments